Characteristics of snow cover in the forest-steppe of Cisbaikalia - E. V. Maksyutova (Лëд и снег)
Statistical parameters and tendencies of the long-term changes in snow cover characteristics of forest-steppe in Fore-Baykal region were evaluated according to the observational data obtained at meteorological stations by means of permanent snow stake as well as using snow survey in the field and in the forest for the long-term period 1961–2000. Duration of snow cover decreases. The snow depth according to the permanent snow stake increases. The observed values of snow survey show that in the field without any significant changes in the snow depth manifest itself the local effect of water supply reduction in the snow cover. The largest rates of decrease of snow depth and snow storage has experienced in the forest. The maximum snow density decreases both in the field and in forest.